2022
DOI: 10.1002/chem.202103967
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Micellar Media in the Synthesis of DNA‐Encoded Libraries

Abstract: DNA-encoded library (DEL) technology has become widely used in drug discovery research. The construction of DELs requires robust organic transformations that proceed in aqueous media under mild conditions. Unfortunately, the application of water as reaction medium for organic synthesis is not evident due to the generally limited solubility of organic reagents. However, the use of surfactants can offer a solution to this issue. Oil-in-water microemulsions formed by surfactant micelles are able to localize hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 87 publications
(82 reference statements)
0
12
0
Order By: Relevance
“…[67][68][69][70] Micellar catalysis involves the formation of micelles effectively around the organic part of the DNA-conjugated moiety, focusing on the desired region of the reacting component, while the DNA part would remain in the aqueous phase without any damage. 71,72 Thus, the use of micelles could be helpful in the diversification of the DEL synthesis, and this section enlists the various developments that have taken place in the past several years.…”
Section: (B) Micelle-mediated Dels Synthesismentioning
confidence: 99%
“…[67][68][69][70] Micellar catalysis involves the formation of micelles effectively around the organic part of the DNA-conjugated moiety, focusing on the desired region of the reacting component, while the DNA part would remain in the aqueous phase without any damage. 71,72 Thus, the use of micelles could be helpful in the diversification of the DEL synthesis, and this section enlists the various developments that have taken place in the past several years.…”
Section: (B) Micelle-mediated Dels Synthesismentioning
confidence: 99%
“…These turned out to also be effective against SARS-CoV-2 main protease [243] and thus provided the key structure-based data for two distinct fruitful hit to lead programs against this virus [78,81,82]. The current generation of DNA-encoded libraries, a technique which stemmed from an academic [244,245] thought experiment and was quickly adopted by industrials [246,247], is also a noteworthy incentive for innovation in organic chemistry [248][249][250][251][252]. However, and still on COVID-19, the DNA-encoded chemical library approach which led to yet another aldehyde-bearing compound effective against SARS-Cov-2 main protease remains to be judged as relevant [253].…”
Section: Suggestions To Improve the Output Of Academic Drug Discovery...mentioning
confidence: 99%
“…We, [11–14] and others, [15] have reported the use of micelle‐forming surfactants to promote on‐DNA reactions that offers a versatile means of carrying out organic reactions in an aqueous medium. The reactions that we have reported proceed with excellent conversion, tolerate a broad substrate scope and use the commercially available surfactant TPGS‐750‐M, providing operationally simple procedures [16] …”
Section: Introductionmentioning
confidence: 99%
“…The reactions that we have reported proceed with excellent conversion, tolerate a broad substrate scope and use the commercially available surfactant TPGS-750-M, providing operationally simple procedures. [16] Given the significance of the Sonogashira reaction in medicinal chemistry, several groups have developed on-DNA Sonogashira couplings. [17][18][19] In one pioneering study, the coupling between aryl fluorosulfonates and alkynes was reported with moderate to high conversion.…”
Section: Introductionmentioning
confidence: 99%